2009
DOI: 10.1007/s11269-009-9471-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Urbanization Factors on Model Parameters

Abstract: This study mainly explores effects of urbanization factors on hydrograph parameters. Urbanization impacts of the developing watershed are evaluated based on rainfall-runoff simulations. A total of 51 rainfall-runoff events occurred from 1966 to 2002. Forty of these were calibrated, and effects of urbanization factors on runoff hydrographs resulting from a simple hydrological model were assessed. The block Kriging method was used to estimate the mean rainfall of the Wu-Tu watershed, and its hourly excesses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…This study concerns the applicability of urbanization variables for regular variations of hydrographic parameters. Previous research showed that changes related to urbanization in watershed divisions may be associated with imperviousness or population density (Cheng et al 2010). Relationships may exist between model parameters and urbanization variables.…”
Section: Correlativity Of Parameter Behaviour and Urbanization Variablesmentioning
confidence: 99%
“…This study concerns the applicability of urbanization variables for regular variations of hydrographic parameters. Previous research showed that changes related to urbanization in watershed divisions may be associated with imperviousness or population density (Cheng et al 2010). Relationships may exist between model parameters and urbanization variables.…”
Section: Correlativity Of Parameter Behaviour and Urbanization Variablesmentioning
confidence: 99%
“…There are several schemes for estimating average rainfall values from raingauge data, including the inverse distance method (Maidment 1993), Thiessen polygon method, height-balanced polygon method, and block Kriging method (Delhomme 1978;Isaaks and Srivastava 1989;Cheng and Wang 2002;Cheng et al 2008b;Huang et al 2008a;Huang et al 2008b;Cheng et al 2010;Cheng 2010b, c). These methods often assign weights to raingauge observations using weighted mean by related observations, and then obtain mean rainfall estimations for specific areas.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in impermeable surfaces connected to a waterway will increase peak stream flows and the risk for flooding or channel erosion. The problems created by impervious cover and subsequent runoff are well-documented and go straight to the center of issues of land use change, urban sprawl, and impacts on the environment and urban riparian ecology (Morse et al 2003;Walsh 2000;Cheng et al 2009). …”
Section: Introductionmentioning
confidence: 99%